110k views
4 votes
Rewrite f(x) = x2 + 12x + 26 in general form. Because both sides of the equals sign will be manipulated, replace the f(x) with the variable y.

User JerSchneid
by
5.5k points

1 Answer

5 votes

Answer:

The equation

f(x) = x^2 + 12*x + 26

can be rewritten as

y = x^2 + 12*x + 26

More information about this equation can be seen in the picture attached below.

Rewrite f(x) = x2 + 12x + 26 in general form. Because both sides of the equals sign-example-1
Rewrite f(x) = x2 + 12x + 26 in general form. Because both sides of the equals sign-example-2
User Matt Tang
by
5.8k points